Cover Feature: Probing the Electrostatic Barrier of Tetrathiafulvalene Dications using a Tetra‐stable Donor–Acceptor [2]Rotaxane (Chem. Eur. J. 28/2020). Issue 28 (28th April 2020) - Jensen, Morten; Kristensen, Rikke; Andersen, Sissel S.; Bendixen, Dan; Jeppesen, Jan O.
Abstract : Control of directionality is of paramount importance if rectified motion in electroactive molecular machines should be realized. As illustrated in the cover artwork, the tetracationic ring (blue) in a tetraoxidized [2]rotaxane can follow two different tracks; it transpires that it is easier for the ring to follow a track in which it has to move across a monopyrrolotetrathiafulvalene dication (dark green) compared to the track in which it moves across a tetrathiafulvalene dication (light green). More information can be found in the Full Paper by J. O. Jeppesen et al. on page 6165 .